The effect of cyriax soft tissue release and myofascial release on pain pressure threshold, flexibility and muscle length in idiopathic adhesive capsulitis- a comparative study - Makwana, Ami; Mishra, Neeti (International Journal Of Community Medicine And Public Health, 2023)
Background: Adhesive capsulitis has been reported to affect 2-5% of the general population and up to 11-30% of subjects with diabetes and thyroid disease. Both myofascial release technique and cyriax soft tissue release technique are effective in patients with adhesive capsulitis. Aims and objective were to assess the effect of cyriax soft tissue release and myofascial release on pain pressure threshold, flexibility and muscle length in idiopathic adhesive capsulitis - a comparative study. Methods: In the present comparative study, total forty-eight (48) patients with Adhesive capsulitis with age between 40-60 years were included. They were randomly divided into two groups: group-A (n=24) and group-B (n=24). Both group received conventional treatment, in addition group-A received myofascial release technique and group-B received cyriax soft tissue release technique. Patients were evaluated pre-intervention (0 week) and post-intervention (4 week) for pressure pain threshold (by means of algometer), for muscle length (by means of measure tape) and for shoulder flexibility (by means of measure tape). Results: Result showed that there was statistically significant difference between MFR group and cyriax group in mean difference of PPT, muscle length and Apley’s test during 4-week intervention period (p<0.05). Conclusions: Cyriax along with conventional treatment is more effective for improving pressure pain threshold, improving muscle length and improving the flexibility of shoulder than myofascial release technique along with conventional treatment in patients with adhesive capsulitis.